2010
DOI: 10.1007/s12105-010-0209-z
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Thyroid Presenting as a Submandibular Mass

Abstract: Although extremely rare, the presence of ectopic thyroid tissue in the submandibular region should be considered in the differential diagnosis of tissue masses in the cervical region. Diagnosis is confirmed by fineneedle aspiration biopsy and exclusion of malignancy should be confirmed by histopathologic analysis of the lesion. In general, surgery is the treatment of choice. A rare case of ectopic thyroid in the right submandibular region is reported; it was diagnosed after total thyroidectomy and successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 17 publications
0
57
0
2
Order By: Relevance
“…The prevalance of ETT is about 1 per 100,000-300,000 people, and 1 in 4,000 to 8,000 patients with the thyroid diseases and male to female ratio is 1/4 (14,15). However, in autopsy studies, the prevalence was found 7-10% (16,17). Ectopic thyroid tissue is most common in older than 40 years, especially in populations of Asian origin (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalance of ETT is about 1 per 100,000-300,000 people, and 1 in 4,000 to 8,000 patients with the thyroid diseases and male to female ratio is 1/4 (14,15). However, in autopsy studies, the prevalence was found 7-10% (16,17). Ectopic thyroid tissue is most common in older than 40 years, especially in populations of Asian origin (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Oropharyngeal examination showed a spherical mass at the back of the tongue but covered with intact mucosa measuring 3-2-2 cm. Thyroid hormone study reveals elevated TSH 43.54 mIU/L but with normal serum T 3 4 pml/L & T 4 9.3 pml/L level suggestive of hypothyroidism. Thyroid ultrasonogram report shows no thyroid tissue in thyroid bed, Thyroid spect scan by Tc99 shows thyroid gland not visualized in thyroid area.…”
Section: Case Reportmentioning
confidence: 96%
“…Thyroid scan can also unmask additional sites of thyroid tissue. Color Doppler US, computed tomography (CT), and magnetic resonance imaging (MRI), may help in designating the extension and location of ectopic tissue, thus contributing to a better pre-surgical evaluation of these cases 4,11,15 .…”
Section: Investigationsmentioning
confidence: 99%
See 2 more Smart Citations